2018
DOI: 10.3390/ma11122437
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Friction Stir Welding Defects of AA1060 Aluminum Alloy Using Specific Damping Capacity

Abstract: The demand for nondestructive testing has increased, especially in welding testing. In the current study, AA1060 aluminum plates were jointed using the friction stir welding (FSW) process. The fabricated joints were subjected to free vibration impact testing in order to investigate the dynamic properties of the welded joint. Damping capacity and dynamic modulus were used in the new prediction method to detect FSW defects. The data acquired were processed and analyzed using a dynamic pulse analyzer lab shop and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Another work by M. Sabbaghian et al [7] revealed that the copper matrix composites prepared with TiC reinforcement, exhibited enhanced hardness and wear resistance due to refined grain structure obtained by FSP. Some other researchers attempted to obtain the dynamic properties of the friction stir welded joints using specific damping capacity with the help of simulation strategies [8]. A review study by V. Patel et al [9] summarizes that the effects of various process variables on the microstructure and physical properties of the aluminium composites prepared by FSP has been attempted in the recent literature.…”
Section: Introductionmentioning
confidence: 99%
“…Another work by M. Sabbaghian et al [7] revealed that the copper matrix composites prepared with TiC reinforcement, exhibited enhanced hardness and wear resistance due to refined grain structure obtained by FSP. Some other researchers attempted to obtain the dynamic properties of the friction stir welded joints using specific damping capacity with the help of simulation strategies [8]. A review study by V. Patel et al [9] summarizes that the effects of various process variables on the microstructure and physical properties of the aluminium composites prepared by FSP has been attempted in the recent literature.…”
Section: Introductionmentioning
confidence: 99%
“…Fabrication of the metal matrix composite has been investigated using different techniques [1][2][3][4]. However, friction stir processing (FSP) is the most advanced method used to fabricate surface and metal matrix composites in a solid-state [5][6][7][8][9][10]. The improvement is due to the stirring action of FSP reflected on the microstructure refinement of the processed material.…”
Section: Introductionmentioning
confidence: 99%
“…The refined grains significantly affect the dynamic properties of alloys and their composites regarding the impedance of the refined grains of the transmitted excitation source. Fewer investigations have discussed the impact of alloying elements on the dynamic properties [30][31][32]; hence, the effect of refined grains in addition to Al 2 O 3 nanoparticles using friction stir processing showed a significant improvement in the dynamic behaviour [33].…”
Section: Introductionmentioning
confidence: 99%